THEORETICAL FOUNDATIONS OF COSTS - Dzhumaeva Guzal Akhtamovna (TADQIQOTLAR, 2025)
Abstract: The article discusses international standards of provision, the corresponding classification of education in national practice and ensuring security in international practice.